(untitled) (American Journal of Islam and Society, 2013)
This paper seeks to provide a sociological reinterpretation of Islam’s presence in the Ado-Ekiti kingdom by unraveling the various essentially sociopolitical and economic factors that, along with religious factors, account for its emergence and growth. I have adopted a historical methodology (narrative) to understand and explain its appearance, functions, and contributions in the kingdom. This will be supplemented with material found in public and private libraries, archives and museums, and artifacts. The paper reveals that the exact date of Islam’s introduction remains unknown and that local Muslims worshipped in secret until 1836, when a Muslim named Ali Atewogboye ascended the throne. He and his successor gave Islam a strong foundation due to their sociopolitical and economic motivations. The paper closes with an account of the factors that facilitated Islam’s spread, the problems faced by local Muslims, and how they have tried to resolve these problems.